Bishop Andrew (Ukhtomsky)’s Activity on Organization of Missionary Work in Sukhumi Eparchy in 1912-1913 (Based on “Employee of the Transcaucasian Mission” Journal Materials) - O. S. Pavlova (Научный диалог)
The work of Bishop Andrew (Ukhtomsky) in the Sukhumi eparchy in 1912-1913 is analyzed, aimed at organizing parish life and missionary and educational work in general. It is shown that an important step in this direction was the creation of the first in the eparchy printed Church missionary journal “Employee of the Transcaucasian mission.” Studying the journal materials allowed to draw conclusions that the wide experience of missionary work, accumulated by Bishop Andrew in the Kazan eparchy, has found application in the new appointment. It is proved that the purpose of the journal “Employee of the Transcaucasian mission” was the implementation of the key tasks of missionary work; it also became a periodical of the Brotherhood of St. Blessed Prince Alexander Nevsky. The article presents the results of the analysis of the materials published in this journal, which contain information on specific activities, as well as reflections on the revival of parish Orthodox life, the organization of pastoral ministry, parish schools, churches, the local Church Archaeological Commission, etc. It is reported that the journal was published till 1916. The author of the article comes to the conclusion that the Ministry of Bishop Andrew in Sukhumi eparchy was reflected and wide developed in the future.